2012
DOI: 10.3390/v4050833
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in Arterivirus and Coronavirus Infections: Do They Protect Against Disease or Enhance it?

Abstract: Regulatory T cells (Tregs) are a subset of T cells that are responsible for maintaining peripheral immune tolerance and homeostasis. The hallmark of Tregs is the expression of the forkhead box P3 (FoxP3) transcription factor. Natural regulatory T cells (nTregs) are a distinct population of T cells that express CD4 and FoxP3. nTregs develop in the thymus and function in maintaining peripheral immune tolerance. Other CD4+, CD4-CD8-, and CD8+CD28- T cells can be induced to acquire regulatory function by antigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 76 publications
(114 reference statements)
1
87
0
5
Order By: Relevance
“…MERS‐CoV and SARS‐CoV are β‐coronaviruses that can cause fatal lower respiratory tract infections and extrapulmonary manifestations 70–72 . T cells, CD4+ T cells, and CD8+ T cells particularly play a significant antiviral role by balancing the combat against pathogens and the risk of developing autoimmunity or overwhelming inflammation 73 . CD4+ T cells promote the production of virus‐specific antibodies by activating T‐dependent B cells.…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…MERS‐CoV and SARS‐CoV are β‐coronaviruses that can cause fatal lower respiratory tract infections and extrapulmonary manifestations 70–72 . T cells, CD4+ T cells, and CD8+ T cells particularly play a significant antiviral role by balancing the combat against pathogens and the risk of developing autoimmunity or overwhelming inflammation 73 . CD4+ T cells promote the production of virus‐specific antibodies by activating T‐dependent B cells.…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%
“…Recent studies have demonstrated induction of Tregs during early phase of acute infection with PRRSV [16][17][18][19][20]. Moreover, the increased frequency of CD25 + FoxP3 + T cells during infection with PRRSV in pigs has been associated with an increased production of the inhibitory cytokines IL-10 and TGF-beta [18,20], lymphocyte suppression activity in vitro [20,32] and increased susceptibility to natural Mycoplasma hyopneumoniae infection [17]. The induction of this T cell subset could explain the decreased and delayed local [33][34][35] and systemic [6] PRRSV-directed cell mediated immunity in PRRS infection, and the generalized immunosuppression observed in acutely infected pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Porcine reproductive and respiratory syndrome virus (PRRSV) usually induces slow and weak anti-viral immune responses, leading to persistent infection and immunosuppression [1][2][3][4][5]. The lack of anamnestic responses observed following PRRSV exposure in previously vaccinated pigs [6,7] implied that even the well-primed immune system was severely impaired during active PRRSV infection.…”
Section: Introductionmentioning
confidence: 97%
“…Interleukin-10 is essential for induction of PRRSV-specific Tregs [15]. The role of PRRSV-specific Tregs has also been linked to delayed induction of cellular responses and increased susceptibility of bacterial infection in infected hosts [5,16,17].…”
Section: Introductionmentioning
confidence: 98%